Driving factors of desertification in Qaidam Basin, China: An 18-year analysis using the geographic detector model. (May 2021) - Han, Jinjun; Wang, Jianping; Chen, Liang; Xiang, Jiangyun; Ling, Zhiyong; Li, Qingkuan; Wang, Erlong
Graphical abstract: Highlights: We used geographic detector method & GIS to determine desertification driving factors. Our study involved bio-, hydro-, & atmosphere, with implications for anthroposphere. Evaporation had the strongest impact on desertification, followed by precipitation. Comprehensive consideration of multiple factors enhanced study of desertification. Abstract: The Qaidam Basin is a cornucopia of salt mineral resources in China, but desertification in the basin has seriously impacted residents' lives and economic development. Comprehensive analyses of the spatial distribution characteristics of desertification and its driving factors will improve understanding of the causes of desertification. To explore these causes and related driving factors, we used the geographical detector model and geographical information system (GIS) techniques to quantify the relative importance and interactions of driving factors, including meteorological, environmental, and human factors. We found that desertification in the southern Kunlun Mountains, eastern Qilian Mountains, and front of the alluvial fan in the northern Kunlun Mountains was low. This was mainly due to the relatively abundant water resources in these areas. Desertification in the central and western Qaidam Basin was high primarily on account of the abnormally high evaporation. The power of determinant value showed that evaporation (0.481) had the strongest impact on desertification, followed by precipitation (0.460), vegetation type (0.360), soil type (0.293), and temperature (0.251). Evaporation has significantly positive effect on the level of desertification, and precipitation has significantly negative effect. Meteorological factors had the greatest impact on desertification, followed by environmental factors, whereas human factors were the least influential. Despite the small population in the basin and limited economic development, the impact of human activities on desertification cannot be ignored. Our results further indicated that the interactions between the driving factors could enhance the evaluation of desertification. This study comprehensively considered three types of impact factor and a total of nine driving factors. It also analyzed the spatial distribution characteristics and driving factors of desertification in the basin, which improved understanding of desertification in such arid and semi-arid regions in northwest China.